THE SIGNIFICANCE OF MODERN LESSONS ON THE FORMATION OF GEOGRAPHICAL CONCEPTS IN THE TEACHING OF NATURAL SCIENCES - Shonazaova Sevara Rashidovna (Scholar Express Journal, 2023)
General education schools in the article formation of geographical concepts in the teaching of natural sciences in primary grades , the role of modern lessons in the educational process , implementation of acquired knowledge, skills, skills and competences in the context of formation of geographical concepts , the phenomenon between nature and society and The aspects of improving the scientific worldview of students by understanding the content and essence of process changes, comprehensively imagining scientific concepts in the content of these educational subjects, and applying them to practice are highlighted.
Keywords: modern lesson; national program; natural sciences